Maxillary Sinus Floor Augmentation With Synthetic Bone Substitutes Compared With Other Grafting Materials: A Systematic Review and Meta-analysis. Issue 3 (June 2018) - Starch-Jensen, Thomas; Mordenfeld, Arne; Becktor, Jonas Peter; Jensen, Simon Storgård
Abstract : Objective: To test the hypotheses of no differences in implant treatment outcome after maxillary sinus floor augmentation (MSFA) with synthetic bone substitutes (SBS) compared with other grafting materials applying the lateral window technique. Materials and Methods: A MEDLINE/PubMed, Embase and Cochrane Library search in combination with hand-search of selected journals was conducted. Results: Five randomized controlled trials with low risk of bias fulfilled the inclusion criteria. SBS disclosed high survival rate of suprastructures and implants with no significant differences compared to autogenous bone graft or xenograft. Meta-analysis revealed a patient-based implant survival rate of 0.98 (confidence interval: 0.89–1.08), indicating no differences between SBS and xenograft. SBS demonstrated significant less newly formed bone compared with autogenous bone graft, whereas no significant difference was revealed as compared to xenograft. High implant stability values, limited periimplant marginal bone loss, and few complications were reported with SBS. Conclusions: There seem to be no differences in implant treatment outcome after MSFA with SBS compared to other grafting materials.